Study on the Impact of Big Data Processing in Electronic Commerce - Yunhai Chen; Lanqiu Huang (Dianxin kexue)
It is difficu1t for traditiona1 IT infrastructure to manage and use the growing massive data in e1ectronic commerce effective1y.In view of it, the impact of big data processing on the deve1opment of e1ectronic commerce was discussed based on discussing the big data.